2022
DOI: 10.1177/13506501221081570
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the structure of a hydrocarbon radical on the antifriction properties of phosphorothionates in biodegradable lubricants

Abstract: The study aim is to develop methods of efficiency enhancement for the antiwear additives in the lubricants based on hydrocarbon oils. The tribological properties of triaryl and trialkyl phosphorothionates with similar hydrocarbyl groups have been compared. The testing has been carried out in the contact unit of combined rolling and sliding friction. It has been shown that trioctyl phosphorothionate is considerably superior to tribenzyl phosphorothionate and triphenyl phosphorothionate in antifriction and antiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Several prior studies by the authors [28][29][30][31] support the concept of the adsorption mechanism of anti-wear additives in hydrocarbon oils. The models developed are based on the physico-chemical principles of secondary polymolecular adsorption of hydrocarbon liquid on metal surfaces that have been modified by surfactants, specifically AW additives.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Several prior studies by the authors [28][29][30][31] support the concept of the adsorption mechanism of anti-wear additives in hydrocarbon oils. The models developed are based on the physico-chemical principles of secondary polymolecular adsorption of hydrocarbon liquid on metal surfaces that have been modified by surfactants, specifically AW additives.…”
Section: Discussionmentioning
confidence: 61%
“…At a load of 392 N, this concentration displayed the maximum effect, resulting in a 1.5-fold reduction in the wear spot diameter from 0.75 mm to 0.5 mm. However, our experimental studies of the contact tests that simulated a plain bearing revealed no discernible difference between the original and additive oils (Figure 3) [29].…”
Section: Methods For Evaluating the Anti-wear Effect Of Additivesmentioning
confidence: 78%
See 2 more Smart Citations